Planning and Integration of Technologies for Effective Implementation of Blended Learning in Universities in Rivers State, Nigeria - Ukaigwe, P. C.; Igbozuruike, Innocent U. (Advances in Social Sciences Research Journal, 2020)
The study investigated planning the integration of technologies in higher institutions as a strategy for effective implementation of blended learning in universities in Rivers State. The design used was descriptive. The population of this study consisted of the 4,377 teaching staff in the three (3) public universities in Rivers State, comprising 2,348 male and 2,029 female teaching staff. The universities are the University of Port Harcourt, Rivers State University and Ignatius Ajuru University of Education. The sample of this study was 590 elements, comprising 327 male and 263 female teaching staff that were drawn from the population using stratified random sampling technique. Instrument of data collection was a questionnaire that yielded a reliability index of 0.84, using test-retest and Pearson Product Moment Correlation techniques. The data generated were analysed using mean to answer research questions. z-test was used to test hypotheses at 0.05 significance level. Findings showed that aligning university’s visions with the aspirations of full integration of blended learning into university system, provision of required communication networking infrastructures and modifying curriculum designs to become deliverable through blended learning mode are key ways of integrating blended learning in the university system. Recommendations made included that university managers should consider seriously, the advantages of blended learning in the school system, with a view to using planning to foster the integration of the learning innovation into the traditional face-to-face teaching and learning approach for improving students learning experiences and achievements.